Evaluation of the diagnostic efficiency of fluorescence in situ hybridization for pulmonary tuberculosis: a systematic review and meta-analysis - Hu, Yu-Qi; Liu, Kang; Lai, Le-Qing; He, Yi-Ru; Hong, Li-Ping; Jiang, Chu-Qian; Liu, Si-Min; Cao, Ming-Zhu (Frontiers in Medicine, 2025)
Objective In clinical practice, an accurate and efficient detection approach for pulmonary tuberculosis (PTB) is highly needed. The fluorescence in situ hybridization (FISH) assay for PTB might be a suitable alternative to current tests. However, a systematic assessment of the diagnostic performance of this new approach is not available. Our study aimed to determine the diagnostic accuracy of FISH for PTB. Methods We examined PubMed and three more databases including Embase, Cochrane Library, and Web of Science databases from their establishment to November 10, 2023, for published articles on the diagnostic performance of FISH on individuals with clinical suspicion of tuberculosis (TB). QUADAS-2 was used to evaluate the literature’s quality. We used Meta-DiSc software to create forest plots. Results The search yielded 7 studies, involving 1,224 sputum samples that could be included in our meta-analysis. The combined FISH sensitivity and specificity were 0.89 (95% CI 0.86–0.92) and 0.98 (95% CI 0.97–0.99), respectively. Furthermore, subgroup analysis was performed based on probes and PTB incidence. Conclusion FISH may be useful in the diagnosis of pulmonary tuberculosis. The sensitivity and specificity of FISH are high for most sputum specimens. Additionally, FISH has better diagnostic performance in countries with low PTB prevalence than in high PTB prevalence countries. We hope this study will find a new and effective tool for the early diagnosis of PTB.